39.5k views
4 votes
Find the radius and center of the circle given by the equation below. (x – 6)2 + (y + 4)2 = 7 r = 7 and center at (-6, 4) r = 7 and center at (6, -4) r = √7 and center at (-4, 6) r = √7 and (6, -4)

User Venning
by
6.0k points

2 Answers

5 votes

Answer:

center at (6, -4) r = √7

Explanation:

(x – 6)^2 + (y + 4)^2 = 7 This is in the form (x – h)^2 + (y - k)^2 = r^2 Where (h,k) is the center of the circle and r is the radius of the circle Rearranging the equation to match this form (x – 6)^2 + (y -- 4)^2 = sqrt(7) ^2 The center is at (6, -4) and the radius is the sqrt(7)

User Rimantas
by
5.7k points
4 votes

Answer:

center at (6, -4) r = √7

Explanation:

(x – 6)^2 + (y + 4)^2 = 7

This is in the form

(x – h)^2 + (y - k)^2 = r^2

Where (h,k) is the center of the circle and r is the radius of the circle

Rearranging the equation to match this form

(x – 6)^2 + (y -- 4)^2 = sqrt(7) ^2

The center is at (6, -4) and the radius is the sqrt(7)

User Gregor Thomas
by
6.1k points